2023
DOI: 10.1182/blood.2022015699
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative diagnosis and impact of acquired von Willebrand syndrome in infants with congenital heart disease

Abstract: AVWS (acquired von Willebrand syndrome) has been reported in patients with congenital heart diseases (CHD) associated with shear stress caused by significant blood flow gradients. Its etiology and impact on intraoperative bleeding during pediatric cardiac surgery have not been systematically studied. This single-center, prospective, observational study investigated appropriate diagnostic tools of aVWS compared to multimer analysis as diagnostic gold standard and aimed to clarify the role of aVWS in intraoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Some assays use ristocetin to trigger vWF-GPIb (vWF:GPIbR) binding and others rely on the spontaneous binding of a gain-of-function recombinant GPIbα fragment that can bind to vWF in the absence of ristocetin (vWF:GPIbM). A recent study reported that measuring the vWF:GPIbM/vWF:Ag ratio is promising as it has a high positive predictive value [15].…”
Section: Discussionmentioning
confidence: 99%
“…Some assays use ristocetin to trigger vWF-GPIb (vWF:GPIbR) binding and others rely on the spontaneous binding of a gain-of-function recombinant GPIbα fragment that can bind to vWF in the absence of ristocetin (vWF:GPIbM). A recent study reported that measuring the vWF:GPIbM/vWF:Ag ratio is promising as it has a high positive predictive value [15].…”
Section: Discussionmentioning
confidence: 99%
“…Hunt et al described lower postoperative levels of ADAMTS13 in the perioperative period of neonates and infants with CHD ( 33 ), which should be taken into account when considering VWF concentrate supplementation. In this context, the introduction of additional routine laboratory parameters such as the VWF:GPIbM/VWF:Ag ratio is a promising possibility for a timely aVWS diagnosis in the perioperative course of paediatric CHD patients ( 34 ). In our opinion, implementation of methods for rapid aVWS detection is necessary and should be available in centers performing neonatal cardiac surgery and providing extracorporeal support.…”
Section: Discussionmentioning
confidence: 99%
“…Kalbhenn et al 318 included the VWF:CB in their study of COVID-19 patients. Icheva et al 319 included the VWF:CB in their study of AVWS in infants with congenital heart disease. Van Den Helm et al 320 included the VWF:CB in their study on pediatric ECMO, reporting changes in VWF multimers, VWF:Ag, and activity; in summary, VWF:Ag increased and HMWM, VWF:RCo/Ag, and VWF:CB/Ag ratios all decreased while patients were on ECMO, compared with baseline pre-ECMO samples and healthy children.…”
Section: The Current Decade—the 2020smentioning
confidence: 99%